Effect of Blanching on the Protein Profile of Bitter Leaf (Vernonia amygdalina) Analyzed by SDS-PAGE - Handayani, Fitri Widya; Wulansari, Shinta (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Blanching is widely employed as a pre-treatment for leafy vegetables to inactivate enzymes and preserve quality. However, its effect on protein integrity in polyphenol rich species remains inadequately characterized. This study evaluated the effect of blanching on the protein profile and protein content of bitter leaf (Vernonia amygdalina). Blanched and non-blanched leaves were extracted using a TCA-based protocol, and protein profiles were analyzed by SDS-PAGE, while protein content was determined by the Kjeldahl method in triplicate. SDS-PAGE revealed distinct protein bands only in blanched samples, whereas non-blanched samples showed no visible bands. Kjeldahl analysis indicated that non-blanched samples had slightly higher protein content (19.20 0.13%) than blanched samples (18.24 0.21%, p < 0.05). These findings suggest that blanching improves protein extractability and electrophoretic detectability, although it slightly reduces total Kjeldahl protein content. Combined qualitative and quantitative approaches are essential for accurate protein assessment in polyphenol-rich plant materials.